PERJANJIAN PENGIKATAN JUAL BELI TANAH DALAM PUTUSAN M.A.R.I NOMOR: 3124K/Pdt/2016 - Martha Hasanah Rustam (Jurnal Ilmu Hukum, 2019)
AbstractThis research focused on two matters of the problem which included how was the Juridical Review of The Binding Sale and Purchase Agreement of Land contained in the Decision of Supreme Court of the Republic Indonesia Number: 3124K/Pdt/2016 and How is the Judge's consideration in the Decision of Supreme Court of the Republic Indonesia Number: 3124K/Pdt/2016. The research method used normative legal research where data is compiled and processed qualitatively to obtain a truth by deciphering the data that has been collected so that the solution can be made of a problem associated with existing theories. The results of this research can be concluded that the Juridical Review of the The Binding Sale and Purchase Agreement on land contained in Decision of Supreme Court of the Republic Indonesia Number: 3124K/Pdt/2016 is SHM number 311 which has been converted into Property Rights Certificate Number 639/Rumbai bukit which is used by Hayatunnupus as collateral at PNM (Persero) is not against the law because the land of the object in accordance with Property Certificate Number 311 is still in the name of Hayatunnupus and has not been declared to switch to Dahniar because there is no evidence of The Binding Sale and Purchase Agreement until it reaches the deed of Sale and Purchase as proof of transfer of land rights repaid and regarding the Judges' Judgments in Decision of Supreme Court of the Republic Indonesia Number: 3124K/Pdt/2016 is to grant a request for cassation from the applicant for the appeal of I HAYATUNNUPUS and Appellant II of PT PNM (Persero) and cancel the Decision of Pekanbaru High Court Number 167/PDT/2015/PT. PBR dated 18 December 2015 which corrected the Pekanbaru District Court Decision  Number 174/Pdt.G/2014/PN.PBR dated April 23, 2015. Keywords: Agreement, Sale and Purchase, Land, Decision of Supreme Court AbstrakPenelitian ini difokuskan pada dua hal rumusan masalah yang meliputi Bagaimana Tinjauan Yuridis Perjanjian Pengikatan  Jual Beli Tanah yang  terdapat dalam Putusan M.A.R.I Nomor: 3124K/Pdt/2016 dan Bagaimana pertimbangan Majelis Hakim dalam Putusan M.A.R.I Nomor: 3124K/Pdt/2016. Metode Penelitian yang digunakan adalah jenis penelitian hukum normative dimana data disusun dan diolah secara kualitatif untuk mendapat suatu kebenaran dengan menguraikan data yang sudah terkumpul sehingga dapat dilakukan pemecahan dari suatu masalah dikaitkan dengan teori-teori yang ada. Hasil penelitian ini dapat disimpulkan bahwa Perjanjian Pengikatan Jual beli tanah yang  terdapat dalam Putusan M.A.R.I Nomor: 3124K/Pdt/2016 adalah SHM nomor 311 yang telah diubah menjadi Sertifikat Hak Milik Nomor 639/Rumbai bukit yang dijadikan Hayatunnupus sebagai agunan di PNM (Persero) tidak bertentangan dengan hukum karena tanah objek perkara sesuai dengan Sertifikat Hak Milik nomor 311 masih atas nama Tergugat I Hayatunnupus dan belum dinyatakan beralih kepada Dahniar karena tidak adanya bukti Perjanjian Pengikatan Jual Beli hingga sampai ke Akta Jual Beli sebagai bukti pengalihan hak atas tanah yang sudah dilunasi dan mengenai Pertimbangan Majelis Hakim dalam Putusan M.A.R.I Nomor : 3124K/Pdt/2016 adalah mengabulkan permohonan kasasi dari pemohon kasasi I HAYATUNNUPUS dan pemohon Kasasi II PT PNM (persero) serta membatalkan Putusan Pengadilan Tinggi Pekanbaru Nomor 167/PDT/2015/PT.PBR tanggal 18 Desember 2015 yang memperbaiki Putusan Pengadilan Negeri Pekanbaru Nomor 174/Pdt.G/2014/PN.PBR tanggal 23 April 2015. Kata Kunci: Perjanjian, Jual Beli, Tanah, Putusan Mahkamah Agung